DOP31 Management and outcome of postoperative Crohn's Disease in the elderly as compared to young adults: Data from Eneida registry. (27th May 2021) - Mañosa Ciria, M; Calafat, M; Ricart, E; Nos, P; Iglesias, E; Riestra, S; López-Sanroman, A; Vera, M; Guardiola, J; Hernández, V; Rivero, M; Carpio, D; et al.
Abstract: Background: A less aggressive phenotype of Crohn's disease (CD) has been reported in patients with elderly onset CD. Despite this, similar surgical rates among younger and older CD patients have been reported. However, scarce data are available about the risk of postoperative recurrence (POR) regarding the age, and no data are available about the use of immunosuppressants and biological agents for prevention of POR in elderly patients. Our aim was to evaluate the management of CD in the postoperative setting and the rate of surgical POR in CD patients according to the age at surgery. Methods: Cohort study including all adult CD patients in the ENEIDA registry (a prospectively-maintained database of the Spanish Working Group in IBD –GETECCU-) who underwent a first intestinal resection with ileo-colonic anastomosis. Patients were grouped regarding their age at the moment of the first surgery: over 60 years (elderly) and between 18 and 60 years of age (controls). Preventive treatment for POR, surgical POR (need for a further intestinal resection) and postoperative morbidity were compared between both groups. Results: Out of the 69, 740 IBD patients included in the ENEIDA database, 3, 982 had a first intestinal resection for Crohn's disease with an ileo-colonic anastomosis between 2005 and 2020. Of them, 535 were elderly and 3, 454 controls. Time from IBD diagnosis to surgery was significantly longer in the elderly (114±128 vs. 93±97 months; p<0.001). Regarding baseline characteristics, the elderly had a lower proportion of penetrating behaviour (25% vs. 39%; p<0.0001) and perianal disease (14% vs. 25%; p<0.0001). No differences were observed in the rate of postoperative morbidity (16% vs 15%; p=0.18). Time of follow-up after surgery was significantly lower in the elderly (63±57.5 vs. 81.2±56 months; p<0.0001). A significantly lower proportion of elderly patients started preventive therapies for POR (immunosuppressants or biological agents) as compared to controls (26% vs . 43%, respectively; p<0.0001). In spite of this, the rates of surgical POR were similar in elderly and controls (19.8% vs . 17.6%, respectively; p=0.169). In the multivariate logistic regression analysis only the inflammatory pattern of the disease was associated with surgical POR (HR 1.27; 95%IC (1.011–1.602)). Conclusion: The elderly patients show similar rates of surgical POR as compared to younger patients. Given the high risk of thiopurine and anti-TNF-related adverse events, elderly patients with inflammatory pattern would benefit from preventive therapy with safer biologicals.